The Thread of Landscape Thinking in China: from the Legacy of West Lake to Ecological Civilization in the 21st Century - Masnou Morera, María José (Sinología hispánica. China Studies Review, 2026)
The civilizing component of the landscape in China justifies the development of this article, why the reading of nature through a cosmology and cultural construction of the landscape for centuries, represents a very significant differential contribution to the reading of nature and man in Western civilization. This text confronts the cultural construct of the landscape in the history of Chinese civilization and the character of green space as a regenerating, balanced, and transforming instrument for cities with serious deficits and environmental problems in the 21st century. We identified the need to connect the distinctive cultural legacy of the landscape of Chinese civilization and the contemporary landscape narrative that emphasize its instrumental value as infrastructure and ecological services.Case studies, West Lake, and two contemporary urban regeneration projects, Xuhui Runway Park and Houtan Urban Park in Shanghai. Western Lake and its surroundings in Hangzhou are a historic reference for their landscape values, to which their physical geography, literary identity, and spatial readability contribute.